The dressmakers of London [large type] - Kelly, Julia, 1986- (Thorndike Press large print dynamic drama., 2025)
"Isabelle Shelton has always found comfort in the predictable world of her mother's dressmaking shop, Mrs. Shelton's Fashions, while her sister Sylvia turned her back on the family years ago to marry a wealthy doctor whom Izzie detests. When their mother dies unexpectedly, the sisters are stunned to find they've jointly inherited the family business. Izzie is determined to buy Sylvia out, but when she's conscripted into the WAAF, she's forced to seek Sylvia's help to keep the shop open. Realizing this could be her one chance at reconciliation with her sister, Sylvia is determined to save Mrs. Shelton's Fashions from closure--and financial ruin. Through letters, the sisters begin to confront old wounds, new loves, and the weight of family legacy in order to forge new beginnings in this lyrically moving novel perfect for fans of Genevieve Graham and Lucinda Riley." -